Application Effect of the 6S Care Model in Sterilization in the Department of Stomatology and Its Impact on the Incidence of Nosocomial Infection. (18th July 2022) - Lou, Jing; Wang, Guiqin; Jiang, Man; Xu, Guochao
Abstract : Objective . The study aimed to explore the effectiveness of the 6S care model in sterilization in department of stomatology and its impact on the incidence of nosocomial infections. Methods . The infection surveillance indicators of the department of stomatology implementing the routine sterilization care model in 2019 were selected as the general group (including 140 patients and 140 cases of oral instrument kits for unpacking), and the infection surveillance indicators of the department of stomatology implementing the 6S care model in 2020 were selected as the 6S group (including 140 patients and 140 cases of oral instrument kits for unpacking). Analysis of the air culture qualification rate of the consultation room + operating room, medical equipment sterilization qualification rate, medical equipment damage rate, incidence of nosocomial infections, satisfaction of medical and nursing staff with instrument sterilization, and patient satisfaction with medical and nursing staff care services under different care models was carried out. Result . The air culture pass rate of the consultation room + operating room in the 6S group was 96.43% (135/140), which was higher than 90.00% (126/140) in the general group, and the difference between the two groups was statistically significant (P > 0.05 ). The sterilization pass rate of medical devices in the 6S group was 100% (140/140), which was higher than 95.71% (134/140) in the general group, and the difference between the two groups was statistically significant (P > 0.05 ). The medical device damage rate in the 6S group was 0.71% (1/140), which was lower than 7.14% (10/140) in the general group, and the difference between the two groups was statistically significant (P > 0.05 ). The incidence of nosocomial infection in the 6S group was 0.71% (1/140), lower than 5.71% (8/140) in the general group, and the difference between the two groups was statistically significant (P > 0.05 ). In the 6S care model, the satisfaction score of 38 healthcare workers with the disinfection of instruments was (96.55 ± 2.40), which was higher than that of the general group (87.79 ± 3.14), and the difference between the two groups was statistically significant (P > 0.05 ). The total nursing satisfaction of the 6S group was 97.86% (137/140), which was higher than 91.43% (128/140) of the general group, and the difference between the two groups was statistically significant (P > 0.05 ). Conclusion . The application of the 6S care model in the sterilization of the department of stomatology can significantly improve the passing rate of infection monitoring indicators in the department of stomatology, reduce the occurrence of medical device damage and nosocomial infection, and have high satisfaction among doctors and patients, which has the value of promotion.